The Function of Activity-Regulated Genes in the Nervous System - LOEBRICH, SVEN (2009)
The mammalian brain is plastic in the sense that it shows a remarkable capacity for change throughout life. The contribution of neuronal activity to brain plasticity was first recognized in relation to critical periods of development, when manipulating the sensory environment was found to profoundly affect neuronal morphology and receptive field properties. Since then, a growing body of evidence has established that brain plasticity extends beyond development and is an inherent feature of adult brain function, spanning multiple domains, from learning and memory to adaptability of primary sensory maps. Here we discuss evolution of the current view that plasticity of the adult brain derives from dynamic tuning of transcriptional control mechanisms at the neuronal level, in response to external and internal stimuli. We then review the identification of “plasticity genes” regulated by changes in the levels of electrical activity, and how elucidating their cellular functions has revealed the intimate role transcriptional regulation plays in fundamental aspects of synaptic transmission and circuit plasticity that occur in the brain on an every day basis.